Forgotten Narratives: Unearthing Social Dynamics and Building Resilience in Micro-Communities of Lesotho - Moshoeshoe, Motsamai (Journal of Asian Multicultural Research for Social Sciences Study, 2023)
This research explores the social dynamics within Lesotho’s micro-communities, shedding light on the intricate interplay of cultural influences, community interactions, and historical resilience strategies. Through qualitative methodologies, the study unveils the adaptive nature of cultural practices, showcasing their role as pillars of community identity and sources of strength during challenges. Community interactions, characterized by reciprocal support and shared responsibilities, emerge as crucial components fostering social cohesion. Historical narratives shape localized resilience strategies, emphasizing the importance of context-specific approaches. The findings contribute nuanced insights to the discourse on community resilience, highlighting the need for tailored interventions that preserve cultural heritage, strengthen social bonds, and acknowledge the historical context of each community.